The Impact of Intelligent Process Automation on Audit and on Junior Auditor’s Skills - Tashkovski, Filip; Zdolšek, Daniel (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Intelligent Process Automation (IPA) has emerged as a transformative force, building on the foundation laid by earlier robotic process automation (RPA) systems. IPA uses advanced technologies such as artificial intelligence, machine learning and cognitive computing to automate more complex processes that are beyond the capabilities of RPA. Implementing IPA requires detailed strategies and training programs for selected employees who will be responsible for this technology. Nevertheless, this does not fully address the fundamental concerns that are causing possible resistance in the audit industry. The dilemma is whether the integration of IPA into day-to-day audit tasks diminishes the professional value and expertise of junior auditors and newcomers to the field. Automation limits junior auditors' exposure to core auditing tasks, leading to skill and experience gaps in risk assessment, data analysis and analytical insights. This dissatisfaction may lead some junior auditors to leave the profession for roles that offer greater skill development and opportunities for professional growth.